Systemic Review and Meta-Analysis on the Surgical Complications in Breast Cancer Patients following Immediate Breast Reconstruction in Patients Received Neoadjuvant Therapy - Saied, Ashraf El Zoghby El; Helmy, Mohamed Ahmed; Abou El Naga, Mohamed Ahmed; Rayan, Mahmoud Talaat; Abd Allah, Mohamed Hussein Makhlouf (QJM : An International Journal of Medicine, 2024)
Background Breast reconstruction (BR) is a unique surgical procedure that provides patients undergoing mastectomy with significant psychosocial and aesthetic benefits and has also become a crucial part of the treatment pathway for women with breast cancer. Aim and Objectives The main aim of this study was to determine the surgical complications in breast cancer patients following immediate breast reconstruction and the effect of neoadjuvant therapy on the surgical complications. Subjects and Methods In this systematic review; we obtained 1,840 citations from the previously mentioned databases. We examined the titles and Abstracts of these references and excluded all the studies that were clearly ineligible for the analysis. For the remaining articles, we obtained full text copies for further evaluation. In the databases that we searched, we obtained 14 potentially eligible studies that examined the influence of NAC on immediate breast reconstruction. Twenty eligible studies addressed the influence of NAC on immediate breast reconstruction, and these studies also included extractable data; they were included in the review and meta-analysis Results A total of 149 donor site complications were founded among included studies and was in form of herniation, infection, hematoma, seroma, fat necrosis, bulging, wound problem, mastectomy skin flap necrosis, capsulectomy Conclusion Immediate breast reconstruction after NACT is a safe procedure with an acceptable post- operative complication profile. It may result in a slight increase in implant loss rates, but it does not delay commencing adjuvant therapy.